Empowering Vietnamese EFL Learners at Tertiary Level: Investigating Factors Shaping Learner Autonomy in English Language Acquisition - Thi Anh Nguyen; Tra Huong Nguyen; My Hoang Nguyen; Thuy Trut Phạm; Thao Thanh Le; Yen Hoang Phuong; Thu Thi Anh Huynh (Universitas Islam Negeri Walisongo Semarang, 2022)
This study scrutinizes the viewpoints of Vietnamese students studying English as a Foreign Language (EFL) regarding determinants impacting their autonomy in English language acquisition. Data was amassed from 117 Vietnamese EFL learners attending a university in Vietnam by using a survey-based methodology. The survey instrument, comprising Likert-type items, was predicated on well-established conceptual frameworks derived from antecedent studies. The study unveiled multiple key influences on learner autonomy, incorporating voluntariness, learner choice, adaptability in study alternatives, peer collaboration, and beliefs about the educator’s role, motivation, capabilities, and independence. These determinants underscore the significance of learners’ active participation, personal agency, social interactions, nurturing learning ecosystems, intrinsic motivation, efficacious learning strategies, and learner empowerment in cultivating learner autonomy. The implications gleaned from these results emphasize the necessity for pedagogical stratagems that encourage voluntariness, learner choice, peer collaboration, teacher backing, motivation, skill enhancement, and learner agency within English language educational environments. These pedagogical stratagems would better equip learners for the autonomous journey of English language acquisition, thereby enhancing the overall efficiency of English language education in the Vietnamese context.